The Importance of the Ijtihad Jama'i Method in Contemporary Fiqh Formulations - M., Pauzi; Hipni, Darul; Radiamoda, Anwar M. (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
The rapid advancement of science, information technology, computers, and the internet has brought about significant changes that have greatly benefited human life. However, along with these advancements, new legal issues have emerged, particularly in the field of muamalah, specifically electronic commerce involving computer and internet technologies. This research explored the importance of collective (jama'i) ijtihad methods in the modern era. A normative legal approach was applied to ascertain the new legal arguments regarding the formulation of contemporary fiqh through the ijtihad jama’i method. This method plays a crucial role in shaping Islamic law to effectively address these emerging problems by involving experts in Islamic law, economics, information and communication technology, and other relevant fields. The results showed that ijtihad jama’i are more robust, closer to the truth, and help avoid conflicts than individual ijtihad.